REPRODUCTIVE CONSTRAINTS AND CONSERVATION STRATEGIES FOR THE ENDANGERED Liquidambar orientalis: IMPLICATIONS FOR RESTORATION ECOLOGY - Volkan Eroglu (Journal of Animal and Plant Sciences, 2025)
Liquidambar orientalis, a relict and endangered species endemic to the Mediterranean region, is of significant conservation concern. Understanding the reproductive biology of this species is crucial for developing effective conservation strategies. This study investigated the reproductive strategy of L. orientalis, focusing on sex ratios, flower developmental stages, stigma receptivity, pollen viability, phenology, and ovule and seed production success. It was determined that L. orientalis had a trimonoecious reproductive system with male, female and hermaphrodite flowers on the same individual. It was discovered that approximately 85% of the inflorescences on the individual had only male flowers, 15% had both male and female or male and hermaphrodite flowers, and that in pistillate inflorescences with both sexes; 30% had female and hermaphrodite flowers at the terminal part of the inflorescence, while 70% had female flowers at the basal part of the inflorescence. In the reproduction of the L. orientalis, the first problem identified as the disadvantage caused by the flowers exhibiting stigma-pollen interaction for a very limited time during the 2.5-month flowering period. Another reproductive challenge was the low success rate of ovule-to-seed conversion, with only 2.25% success in terminal pistillate flowers and 5.8% in basal pistillate flowers, primarily due to the constraints of maternal resource allocation. Consequently, the low reproductive success of this rare species suggested that L. orientalis would struggle to regenerate naturally if its habitats are compromised. As a solution, we emphasized the importance of identifying populations with the highest reproductive success in their natural habitats, establishing gene conservation areas for seed breeding, and prioritizing restoration efforts using seeds from these genetically diverse populations, rather than relying on monoclonal propagation techniques, to preserve the genetic pool of the species.
Keywords: Liquidambar orientalis; Reproductive biology; breeding system; forest conservation